Viral analysis of tumor-bearing chicken flocks in Turkey over the last decade (2011-2020) - Abayli, H; Tonbak, S; Ozbek, R; Karabulut, B (Journal of the Hellenic Veterinary Medical Society, 2023)
Marek’s disease virus (MDV), avian leukosis virus (ALV), and reticuloendotheliosis virus (REV) are important viral agents associated with neoplastic diseases that cause economic losses for the poultry industry worldwide. Immunosuppressive agents such as infectious bursal disease virus (IBDV), REV, and chicken anemia virus (CIAV) expose birds to other infections and reduce production performance. In this context, we aimed to identify and perform molecular analysis of the aforementioned viral infections (ALV, CIAV, IBDV, MDV, and REV) in the tissues of tumor-bearing chickens. Clinical samples were taken from 11 chicken flocks of different ages and races from some provinces (Adıyaman, Diyarbakır, Elazığ and Malatya) in Turkey between 2011 and 2020. MDV positivity was determined in all 11 chicken flocks, while ALV endogenous sequences were determined in two of 11 MDV positive chicken flocks. CIAV and ALV sequences were found together in two of 11 MDV positive chicken flocks. The ALV subgroup J, IBDV, and REV were not detected in any of the chicken flocks. According to phylogenetic analysis, Turkish MDV strains obtained from this study were included in two different genogroups (genogroups I and II) with other MDV strains with pathotypes ranging from virulent (v) to very virulent plus (vv+). Co-infections of ALV and CIAV with MDV may worsen the current clinical situation. In this study, MDV was detected in two flocks vaccinated with HVT. Other chickens were not vaccinated against any of the viral agents studied. Increasing vaccination and preventive measures against these viral pathogens in poultry in Turkey is recommended.